Overview of diabetic kidney disease - Upadhyay, Ashish (Henry Stewart Talks, 2023)
Overview of Diabetic Kidney Disease (DKD), DKD epidemiology and natural history, DKD Pathogenesis, DKD management, Variabilities in DKD trajectory, SGLT2 inhibition in CKD, ACCORD study, Finerenone in DKD: FIDELIO-DKD trial